Evaluation of an Oral Health Promotion Program Designed for Pre-School Children in Ameneh Orphan Center - Parisa Aref; Afsaneh Pakdaman (Tehran University of Medical Sciences, 2012)
Background and Aims: High level of caries was reported in pre-school children at the national level. Due to importance of focusing on high-risk children, this study was carried out to evaluate an oral health promotion program designed for Ameneh orphan center.Materials and Methods: Two centers were chosen and assigned to intervention (Ameneh orphan center) and comparison (Shobeir orphan center). Dental examination has been carried out using dental mirror and blunt probe under artificial light and dmfs index was recorded. Health promotion program including topical fluoride application after dental treatment as well as power point education session for caregivers was delivered in intervention group. Children in the other center were only received routine dental treatment. Data were analyzed using Mann-Whitney and regression tests.Results: 79 children in the intervention group and 51 children in comparison group were evaluated in the study. The mean age of children in the intervention group was 4.7 (SD=1.6) and in the comparison group was 4.6 (SD=1.2). The dmfs index in the intervention and comparison groups was 6.86±10.23 and 8.75±12.42 (NS), respectively. The mean dmfs after intervention in the intervention group was 7.93±11.21 and in the control group was 9.88±12.51, which showed no significant difference (P>0.05). Comparison in subgroups showed that the mean dmfs in the group received fluoride varnish in addition to complete dental treatment was significantly less than the comparison group (P<0.05). Controlling the effect of baseline caries and age on the outcome variable with regression analysis showed that the effect of baseline caries should be considered when comparing two groups.Conclusion: Oral health promotion programs including topical fluoride application can be used in high-risk groups of children.